A cross-sector priority setting method: Critical gaps in malaria research in Tanzania - Temel, Tugrul (International Service for National Agricultural Research, 2004)
This paper describes a new priority setting method for identifying critical information gaps in a multisector system. This method characterizes the information structure of the system using graph-theoretical concepts. Its application is illustrated in the context of malaria research in Tanzania. This illustration reveals two critical pathways, EVHA and EVHPA, which warrant better understanding. The first suggests that malaria research should generate information on the effects of environmental changes (E) on vector ecology (V) and then on the effects of Von human health (H) and then on the effects of H on agriculture (A). Interpreted likewise, the second pathway points to the additional need for information on the effects of socioeconomic conditions (P) on A.